2022
DOI: 10.5194/amt-15-2767-2022
|View full text |Cite
|
Sign up to set email alerts
|

The polarimetric characteristics of dust with irregular shapes: evaluation of the spheroid model for single particles

Abstract: Abstract. In the atmosphere, the dust shapes are various, and a single model is difficult to represent the complex shapes of dust. We proposed a tunable model to represent dust with various shapes. Two tunable parameters were used to represent the effects of the erosion degree and binding forces from the mass center, respectively. Thus, the model can represent various dust shapes by adjusting the tunable parameters. To evaluate the applicability of the single spheroid model in calculating the optical propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The spectral dependence of the dust lidar PDR is indeed instructive (Burton et al, 2016;Haarig et al, 2022;Miffre et al, 2020). Outlooks of this work are obviously also interesting, as underscored by recent papers (Kahnert et al, 2020;Luo et al, 2022), discussing the ability of the spheroidal model to mimic light scattering by complex-shaped mineral dust.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The spectral dependence of the dust lidar PDR is indeed instructive (Burton et al, 2016;Haarig et al, 2022;Miffre et al, 2020). Outlooks of this work are obviously also interesting, as underscored by recent papers (Kahnert et al, 2020;Luo et al, 2022), discussing the ability of the spheroidal model to mimic light scattering by complex-shaped mineral dust.…”
Section: Discussionmentioning
confidence: 77%
“…Depending on the assumed shape model, the lidar PDR can be very different with induced variations in the lidar-retrieved dust mass concentrations (Mehri et al, 2018). Recently, Luo et al (2022) and Huang et al (2022) discussed the ability of the spheroidal model to mimic the complex shape of mineral dust. Likewise, Zubko et al (2013) found spheroids inadequate for describing the dust particles' spectral dependence of the lidar PDR.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral dependence of the dust lidar 𝑃𝐷𝑅 is indeed instructive (Burton et al, 2016;Haarig et al, 2022;Miffre et al, 2020). Numerical outlooks of this work are obviously also interesting, as underscored by recent papers (Kahnert et al, 2020;Luo et al, 2022), discussing on the ability of the spheroidal model to mimic light scattering by complex-shaped mineral dust.…”
Section: Discussionmentioning
confidence: 73%
“…Depending on the assumed shape model, the lidar 𝑃𝐷𝑅 can be very different with induced variations in the lidar-retrieved dust mass concentrations (Mehri et al, 2018). Recently, (Luo et al, 2022) discussed on the ability of the spheroidal model to mimic the complex shape of mineral dust. Likewise, (Zubko et al, 2013) found spheroids inadequate for describing the dust particles' spectral dependence of the lidar 𝑃𝐷𝑅.…”
mentioning
confidence: 99%